ChemInform Abstract: Artificial Photosynthesis at Dynamic Self‐Assembled Interfaces in Water. Issue 11 (February 2016) - Hansen, Malte; Troppmann, Stefan; Koenig Burkhard, Koenig Burkhard
Abstract: Review: applications of micellar and vesicular microheterogeneous systems for solar energy conversion by photosensitized water oxidation and hydrogen generation; 44 refs.